NASKAH DRAMA “JENGGIT CEMBENG” KARYA TRISNO SANTOSO SEBAGAI ALTERNATIF BAHAN AJAR TELAAH NASKAH SANDIWARA PADA SISWA SMP (ANALISIS STRUKTURAL DAN NILAI PENDIDIKAN KARAKTER) - Setyawan, Bagus Wahyu; Suryanto, Edy; Kurwidaria, Favorita (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2017)
This research have purposes for describe (1) drama text structure of “Jenggit Cembeng” creation of Trisno Santoso, (2) character education values on “Jenggit Cembeng” creation of Trisno Santoso, and (3) compatibility drama text “Jenggit Cembeng” creation of Trisno Santoso as alternative learning material on drama text study on Lower Secondary School students. Method of this research is descriptive qualitative research. Data resource on this research is document and informan. Content analysis and interview technical is using for collected data. Furthermore, data is ben analysis and then checked using resource and theory triangulation. Result of this research is: (1) structural result analysis is theme on this text is about human capability to manage egoistic. Theme of the text is related with chracters, that is the main or protagonist characters (Pak Wida and Bima) which have function to bring theme of story. Except protagonist characters, there are antagonist characters (Bu Mahanani and Panjang), tritagonist characters (Senen, Arum, Si Mul, and Palupi), and accomplice characters (Polisi, Tiar, and his friends). This text is using progressive plot and settle, based from time setting. Dialogue is using Javanese language register. Dialog have function to explain conflict, is talk about family and teenager conflict. Technical direction is written using capital letter and put on brackets sign. Furthermore, command from this text is context with theme of this text, that is importance to manage egoistic on our self so that can live in harmonious; (2) There are character education values including on this text. The most dominant is value about responsibility and hardworking based from the main characters; (3) Furthermore, this text will gived for teacher to conclude as alternative learning material on drama text study on SMP students, because have completed learning material criteria based from language, story, and character education values in this text.